Experiences of education of hungarian and international students participating in economic training - Tóth, Eszter Ilona; Horváthné Kovács, Bernadett; Szőke, Brigitta (Acta Carolus Robertus, 2024)
The number of international students in Hungary has been increasing for years, especially since the introduction of the Stipendium Hungaricum in 2013. This fact also justifies the need to deal separately with the education and educational background of international students. In addition to the examination of the international students, the education of Hungarian students is also in focus, our main goal is to compare the two groups: to explore the similarities and differences. The empirical results provide a basis for the subsequent questionnaire survey.Our present study is the prologue and foundation of the beginning of a research. In the current phase of the research, we would like to present the differences in the education of full-time Hungarian and international students studying at the Hungarian University of Agriculture and Life Sciences, Károly Róbert Campus, in bachelor and master courses across several areas, such as their motivation, preparation for classes and theses, etc. The current empirical fact-finding is the first step of our research, from now on we will base the verification or rejection of our assumptions on a questionnaire-based and an in-depth interview.